Shipping Insurance Policies for Mariners./Protection and Indemnity Management. - Klisaris Chrisanthy (2013)
Introduction, Overview of the Protection and Indemnity Insurance in Shipping, Protection and Indemnity Keys, Historical Review of the Main Directives Upon Marine Pollution and Policies, IMO's Liability and Compenssation Conventions, Protection and Indemnity Towards 'Green', Perspectives, Further on Pro Acting Reacting and Acting in Protection and Indemnity Clubs, Conclusion, References.